Empowering Women in Sport Analyzing Sponsorship: Trends and Opportunities for Growth - Elyasi, Siroos; Biniaz, Seyyed Abbas; Naderi Nasab, Mehdi (Psychology of Woman Journal, 2024)
Objective: This narrative review aims to analyze current sponsorship trends in women’s sports, identify opportunities for growth, and provide actionable recommendations for stakeholders, including athletes, sponsors, and policymakers. Methods and Materials: A comprehensive literature review was conducted using sources from academic databases, industry reports, and credible sports marketing literature. The review included studies published in English over the past 15 years. Thematic analysis was employed to identify key trends, challenges, and opportunities in the sponsorship landscape of women’s sports. Findings: Findings indicate a growing recognition of the commercial and social value of sponsoring women’s sports, driven by changing societal attitudes and advocacy for gender equality. Key players in the sponsorship ecosystem include corporate sponsors, sports organizations, media outlets, non-profits, and athletes. Successful sponsorship strategies leverage digital platforms and social media to enhance visibility and engagement. However, significant disparities in financial investment, media coverage, and public perception persist. The review highlights several untapped markets and opportunities for strategic sponsorship, particularly in emerging regions and niche sports. Conclusion: The review points out to the need for a strategic and collaborative approach to sponsorship in women’s sports. By addressing existing disparities and leveraging unique opportunities, stakeholders can drive substantial progress towards gender equality in sports. Enhanced sponsorship not only benefits female athletes and teams but also contributes to broader societal goals of social justice and empowerment.